2016
DOI: 10.1158/1078-0432.ccr-15-0373
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Novel Molecular Subtypes of Small Intestinal Neuroendocrine Tumor

Abstract: Purpose: Small intestinal neuroendocrine tumors (SINET) are the commonest malignancy of the small intestine; however, underlying pathogenic mechanisms remain poorly characterized. Whole-genome and -exome sequencing has demonstrated that SINETs are mutationally quiet, with the most frequent known mutation in the cyclin-dependent kinase inhibitor 1B gene (CDKN1B) occurring in only ∼8% of tumors, suggesting that alternative mechanisms may drive tumorigenesis. The aim of this study is to perform genome-wide molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
157
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(171 citation statements)
references
References 31 publications
(28 reference statements)
12
157
2
Order By: Relevance
“…However, in our larger analysis in this study, we found that copy-number loss and promoter methylation could explain the decreased expression of FBP1. FBP1 promoter methylation downregulated FBP1 expression in patients with basal-like breast cancer (7), gastric cancer (32), and small intestinal neuroendocrine tumor (33). Copynumber loss of FBP1 was also observed in ccRCC cases (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our larger analysis in this study, we found that copy-number loss and promoter methylation could explain the decreased expression of FBP1. FBP1 promoter methylation downregulated FBP1 expression in patients with basal-like breast cancer (7), gastric cancer (32), and small intestinal neuroendocrine tumor (33). Copynumber loss of FBP1 was also observed in ccRCC cases (34).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the most frequent genomic alteration is hemizygous deletions affecting chromosome 18q (133,136,137,139). Recent data have shown that SI-NETs can be sub-classified based on tumor methylome into three distinct clusters (140,141). Sub classification of SI-NETs based on gene expression may also provide relevant information (142).…”
Section: Small Intestinal Netsmentioning
confidence: 99%
“…However, NETs of the small intestine (SI-NETs) are the most common tumors of this part of the gastrointestinal system [1] and have experienced a dramatic increase in incidence over the past three decades [2] . SI-NETs are tumors with low rates of somatic mutations, as shown in 2 recent studies involving the analysis of 48 and 180 SI-NETs, respectively, by massive parallel sequencing, which revealed a mutation frequency (single nucleotide variants; SNVs) of approximately 0.1 per 10 6 nucleotides. PI3K/Akt/mTOR signaling molecules showed copy number changes in 29% of the analyzed cases.…”
Section: Introductionmentioning
confidence: 97%
“…SERPINB5 , coding for maspin. In addition, the authors were able to classify SI-NETs in three distinct subgroups, with the Chr18 LOH group being the most favorable and significantly associated with reduced global methylation status [in contrast to no copy number variations (CNVs) and multiple CNVs] [6] . Although these recent reports gave important new insights into the genetic events in SI-NET, not one of the putative tumor suppressors or oncogenic proteins has been studied at the protein level.…”
Section: Introductionmentioning
confidence: 99%